Effect of Non-Hexane Fraction of Ethanol Extract of Noni Fruit (Morinda citrifolia L.) on ALT Activities, Creatinine Levels and TCD4+/TCD8+ Cell Ratios in The Isoniazid-Induced Female Rats - Ekawati, Nuraini (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2017)
Isonicotinyl hydrazine (isoniazid) is the most effective drug for antituberculosis treatment. During the metabolism process of isoniazid, some reactive metabolites might be generated. Thus reactive metabolite possibly responsible for several side effect through the mechanism of oxidative stress. Some of the side effects are liver damage, kidney damage, and autoimmune disorder characterized by decreased TCD4+/TCD8+ cell ratio.               Noni (Morinda citrifolia L.) contains phenolic compounds such as scopoletin, quercetin, and rutin, which have various biological activities including antioxidant, antiinflammatory, and hepatoprotective activities. The antioxidant activity of phenolic compounds is through the mechanism of radical scavenging, inhibit formation of free radicals, therefore tissue damage can be prevented.The purpose of this study was to determine chemical constituens of non n-hexane fraction of Noni fruit extract (test sample) and to determine whether test sample can reduce the side effect of isoniazid by measuring ALT activity, creatinine level, and TCD4+/TCD8+ cell ratio. Total 35 Wistar rats, aged 6-8 weeks, were divided into 7 groups. Group I as normal control group received 0.25% DMSO, group II received isoniazid 150 mg/kgBW, group III received ethanol extract of Noni fruit 250 mg/kgBW, group IV received isoniazid 150 mg/kgBW + test sample 15 mg/kgBW, group V received isoniazid 150 mg/kgBW + test sample 30 mg/kgBW,  group VI received isoniazid 150 mg/kgBW + test sample 75 mg/kgBW, and group VII received test sample 75 mg/kgBW, each with a volume of 20 mL/kg per oral/day for 8 weeks. Blood samples was collected at weeks 0, 4, 6 and 8 to evaluate the ALT activity, creatinine level, and TCD4+/TCD8+ cell ratio taken. Chemical constituens of test sample was conducted using TLC method.Qualitative analysis indicated that test sample contains alkaloid, phenolic, and flavonoid compound. Test sample could reduce ALT level and increase TCD4+/TCD8+ cell ratio, but couldn’t reduce creatinine level of isoniazide-induced female Wistar rat.